Literature Review Pemanfaatan Cangkang Kerang Sebagai Absorben Limbah Kimia: Pendekatan Ekologi Lingkungan Untuk Pengelolaan Sumber Daya Alam yang Berkelanjutan - La Alio; Hasim Hasim; Dewi Wahyuni K. Baderan (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
The utilization of clam shells as adsorbents has attracted considerable attention due to their ability to adsorb contaminants such as heavy metals, hazardous substances, and oil. Clam shells, which are composed mainly of calcium carbonate (CaCO₃), possess a porous structure that favors adsorption. Calcium carbonate imparts alkaline properties that neutralize acidic effluents and promote the formation of precipitates. Physical and chemical modifications can enhance the surface area and porosity of the shell, thereby enlarging the active sites for contaminant sorption. Clam shells heavy metals such as Pb, Cd, Hg, organic substances and can be used for oil spill remediation due to their hydrophobic and oleophilic properties. The calcination process converts the shells into a material that contaminants such as TSS, COD, and BOD. This utilization not only mitigates pollution but also creates opportunities for adsorbent products with economic value, especially in coastal areas where shell waste is abundant. However, this application must take into account ecological and health impacts, as overharvesting and non-environmentally friendly processing can damage the ecosystem. A sustainable approach with environmentally friendly regulations and technologies is essential to maximize the benefits of clam shells as adsorbents.